PENGARUH MUSIK KLASIK DAN PREFERENSI PRIBADI TERHADAP TEST ANXIETY DAN HASIL TES MEMBACA KOMPREHENSIF SISWA [THE EFFECT OF CLASSICAL MUSIC AND PERSONAL MUSIC PREFERENCE ON TEST ANXIETY AND READING COMPREHENSION TEST RESULTS] - Andreas Sigit Pamungkas (Jurnal Teropong Pendidikan, 2021)
Music is part of human life. Studies show that music influences psychological, cognitive, behavior, and emotion sides of human being. Research shows that music also influences students’ performance on reading comprehension test and test anxiety level. The purpose of this study is to investigate the effect of classical and personal preference music on students’ reading comprehension test performance and test anxiety level at grade XII SMAK 4 PENABUR Jakarta. The experiment design of this study is Pretest Posttest Non-Randomly Assigned Design. The students in experiment group get a treatment that is listening to classical music fifteen minutes before and while doing reading comprehension test. Students in another experiment group get a treatment that is listening personal preference music fifteen minutes before and while doing reading comprehension test in English class. Mean obtained from pretest and posttest of experiment class will be compared with mean from pretest and posttest of control class to explain whether or not they are statistically different. The study shows that classical and personal preference music influence students’ reading comprehension performance and test anxiety. Study also shows that there is negative correlation between students’ test anxiety and reading comprehension performance.